Patient Sharing and Health Care Utilization Among Young Adults With Congenital Heart Disease. (October 2021) - Hardy, Rose Y.; Keller, David; Gurvitz, Michelle; McManus, Beth; Varda, Danielle; Lindrooth, Richard C.
Transitions from pediatric to adult care by young adults with chronic conditions are fraught with challenges. Poor transitions lead to discontinuities of care that are avoidable with better communication between providers. We tested whether exposure to providers with sustained patient-sharing relationships resulted in fewer emergent admissions of young adults with congenital heart disease (CHD). Care transitions are particularly important for young adults with CHD. Though it is not possible to avoid planned admissions for scheduled procedures, emergency admissions are avoidable with proper care. We tested whether several different patient-sharing relationship measures influenced emergent admissions and found that compared with less severe CHD patients, those with severe CHD experienced a 4 to 10 percentage point decline in emergent admissions given a 5 percentage point increase in practice-level patient-sharing relationships. These results are consistent with our hypothesis that patient sharing improves communication and continuity of care across providers, especially for severe CHD patients.